PENGARUH MANAJEMEN SDM DAN BUDAYA ORGANISASI TERHADAP KUALITAS PELAYANAN PADA KANTOR KECAMATAN TAMALATE KOTA MAKASSAR - Dahlan, Dahlan Lan; Iriawan, Hermanu (Departemen Ilmu Administrasi FISIP UNHAS, 2018)
AbstractIn improving service quality Tamalate faced District Office on the quality of Human Resources and Organizational Culture is always oriented to quality services in an effort to meet the needs and expectations of society. The purpose of this study were (i) to analyze the influence of human resource management of the quality of service at the District Office Tamalate Makassar; (Ii) to analyze the influence of organizational culture on quality of service at the District Office Tamalate Makassar; (Iii) to analyze the influence of human resource management and organizational culture on quality of service at the District Office Tamalate Makassar. The samples are saturated samples that use the entire population as a sample of 19 employees. Data collection methods used were observation, interviews, and questionnaires. Data were analyzed with simple regression with SPSS 20:00 for windows. The results showed: (i) human resources management a significant effect on the quality of service Tamalate Makassar City District Office; (Ii) Organizational culture significantly influence service quality Tamalate City District Office; (Iii) human resource management and organizational culture together affect the service quality Tamalate Makassar City District Office.Keywords: Human Resource Management, Organizational Culture and Quality of Service.